Barriers for local sustainable development in Polish communes: insights from the Lubelskie Voivodeship - Witkowski, Jacek (Bariery dla lokalnego rozwoju zrównoważonego w polskich gminach: spostrzeżenia z województwa lubelskiego, 2019)
The purpose of the study is the identification of the limitations which may concern local sustainable development and resulting from the previous scale and directions of activities taken by local self-governments in the scope of protection and use of natural resources. By the example of the group of 49 mayors from the Lubelskie Voivodeship it has been found that the engagement of local authorities in activities contributing to an environment-friendly development in their communes was rather limited. In many cases, there is no reliable identification of existing natural potential and the local authorities are not ready to allocate the funds for various objectives associated with environment protection. The number of officials with the education enabling them to make the right decisions is usually very limited. Another problem is the still recognizable tendency to issue environmental decisions without a previous assessment of the investment impact on the environment
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 12, s. 207-219